Mengembangkan Pendidikan Karakter Berbasis Budaya Menuju Society 5.0 - Everhard Markiano Solissa; Auliya Aenul Hayati; Trisna Rukhmana; Suhari Muharam; Budi Mardikawati; Irmawati Irmawati (Journal on Education, 2024)
Culture-based character education is crucial in shaping individuals who can adapt and contribute positively in the era of Society 5.0, marked by digital transformation and the complexity of global challenges. This research explores the role of local cultural values as the primary foundation for the development of students' character. Through in-depth interviews and document analysis, values such as mutual cooperation, respect for others, and local wisdom are identified as key elements shaping character. The integration of technology in character education is also investigated as a key factor in achieving Society 5.0 goals, with findings indicating that technology can enrich educational experiences and provide broader access to cultural values. Active collaboration among schools, technology, and parents emerges as a strong foundation in shaping characters aligned with desired cultural values. The alignment of the curriculum with local cultural contexts is also found to be a determinant of the successful transfer of character values. Practical implications of this research include the need for policy revisions, teacher training, and collaborative programs to strengthen the implementation of culture-based character education in achieving the vision of Society 5.0. Thus, this research provides a significant contribution to the understanding and implementation of relevant and responsive character education in the dynamics of modern society.